Mitochondrial Genomes of Two Bombycoidea Insects and Implications for Their Phylogeny - Zhao-Zhe Xin (Nature Portfolio, 2017)
Abstract The mitochondrial genome (mt genome) provides important information for understanding molecular evolution and phylogenetics. As such, the two complete mt genomes of Ampelophaga rubiginosa and Rondotia menciana were sequenced and annotated. The two circular genomes of A. rubiginosa and R. menciana are 15,282 and 15,636 bp long, respectively, including 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes and an A + T-rich region. The nucleotide composition of the A. rubiginosa mt genome is A + T rich (81.5%) but is lower than that of R. menciana (82.2%). The AT skew is slightly positive and the GC skew is negative in these two mt genomes. Except for cox1, which started with CGA, all other 12PCGs started with ATN codons. The A + T-rich regions of A. rubiginosa and R. menciana were 399 bp and 604 bp long and consist of several features common to Bombycoidea insects. The order and orientation of A. rubiginosa and R. menciana mitogenomes with the order trnM-trnI-trnQ-nad2 is different from the ancestral insects in which trnM is located between trnQ and nad2 (trnI-trnQ-trnM-nad2). Phylogenetic analyses indicate that A. rubiginosa belongs in the Sphingidae family, and R. menciana belongs in the Bombycidae family.